A Compact Microstrip Lowpass Filter with Flat Group-delay and Ultra High Figure-of-Merit - M. Hayati; M. Ekhteraei; F. Shama (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a new design of a microwave low pass filter (LPF) using coupled stepped impedance patches. The designed LPF has specifications such as ultra sharp roll-off, ultra wide stopband, low insertion-loss and high return-loss in the passband. The designed LPF has -3 dB cut-off frequency of 1.38 GHz. The transition-band is 0.12 GHz that is from 1.38 to 1.50 GHz with the attenuation levels of -3 and -20 dB, respectively. Maximum insertion-loss at about 80% of the passband is 0.1 dB. The simulation and experimental results are close to each other. The proposed LPF achieved to a remarkable figure-of-merit of 171622.